(untitled) (Semiárida, 2020)
The objetive of this study was to evaluate dry matter (DM) rumen degradation kinetics of cultivars (cvs) of small grain pastures. Cultivars were: avena (Avena sativa L.) cv Don Victor, avena (Avena byzantina C. Koch) cv Millauquén, cebada (Hordeum vulgare L.) cv Ullaiché, centeno (Secale cereale L.) cvs Choiqué y Naicó, tricepiro (Triticum x Secale x Thinopyron) unea 3/40 y triticale (x Triticosecale Witt.) cvs Don Norman y Tehuelche. Each plot was cuftour times, on the followingdates: June r-, August 12th, September 30th and November 30th The harvested forage, dried and milled, was incubated in the rumens into suspended nylon bags. Three Holstein-Freisian steers, titted with permanent rumen canulae were used in the experiment. Animals were fed on ad libitum alfalfa hay and water. Ruminal degradability was estimated using DM rate of disappearance, through an exponential model p = a + b(1- exp(-ct)). Data were compared by ANOVA, under a split-plot design Treatment mean were separated using Tukey’s test (α= 0.05). Most differences between cultivars in effective degradability were given by differences in the soluble:insoluble potentially degradable fractions ratio, and due to different fractional rates of degradation. Non-degradable fraction was similar (p>0.05) between cultivars.